PEMBUATAN ARANG RENDEMEN TINGGI DARI TEMPURUNG KELAPA DENGAN KILN DRUM - Nurmala Hudaya; Hartoyo Hartoyo (Jurnal Penelitian Hasil Hutan, 1990)
The aim of  this  research  is to  improve charcoal kiln and production  techniques so  that  yield  and  quality  can be optimazed  with  less capital  operating  cost.The  kiln used in this  experiment  was  made   from a  typical 200 litre oil drum with  special design  incorporating 12  holes  of  13  mm in  diameter in different elevations, at  the  base, 30 cm and 60 cm  above  the  base. A  short  chimney of  30 cm  height  at  the  top  with  10 cm  in  was also  installed  diameter.This report discusses the experimental procedures including raw material preparation, loading and operation of tedrum kiln. The yield all qualities of  the charcoal produced are also  discussed  in  this  report. The  results of this experiment showed that single Drum Kiln can produce high charcoal yield  ranging  from  33,8  % to 37,2 % and average of  35,7 %.A comparison of  results with survey  data  shows   that  the  quality of  the  coconut   shell  charcoal produced  by  the drum kiln  method.  conform favorably with the  quality   of  charcoal  being  used for production of  commercial  activated carbon.